(untitled) (Cardiovascular Journal, 2012)
Atrial tachycardia is a relatively uncommon form of SVT. Atrial tachycardia can be observed in persons with normal heart and in those with congenital heart disease and particularly after surgery for repair or correction of congenital or valvular heart disease. Atrial tachycardia tends to be refractory to pharmacologic therapy and is therefore frequently treated with ablative therapy. If untreated, it may lead to tachycardia-induced cardiomyopathy. So, atrial tachycardia needs to be discussed for recognition and appropriate management. We have gone through different journals to review the latest informations about atrial tachycardia. DOI: http://dx.doi.org/10.3329/cardio.v4i2.10461 Cardiovasc. j. 2012; 4(2): 164-170